Cутність і структура самоосвітньої компетентності майбутніх юристів - Лисицький, М. Ю.; Lysytskyi, M. Yu. (Наука і техніка сьогодні. - 2024. - № 6(34). - С. 532-547, 2024)
Досліджено проблеми формування самоосвітньої компетентності майбутніх фахівців в освітньому процесі закладу вищої освіти. Проаналізовано різні підходи до трактування сутності поняття «самоосвітня компетентність». Обгрунтовано, що самоосвітня компетентність є професійно значущою характеристикою юристів (адвоката, судді, прокурора та ін.), оскільки їхня професійна діяльність вимагає постійної самостійної роботи із законодавчими та нормативно-правовими документами, які постійно оновлюється. Доведено, що зміст самоосвітньої компетентності майбутніх юристів складають: знання щодо раціонального планування, організації та здійснення самоосвітньої діяльності, уміння і навички самоосвітньої діяльності, сукупність мотивів здійснення самоосвітньої діяльності, сформованість емоційно-вольових якостей, рефлексивних вмінь.

The article is devoted to the study of the problem of the formation of self-educational competence of future specialists in the educational process of a higher education institution. On the basis of the review and generalization of the scientific researches of scientists, various approaches to the interpretation of the essence of the concept of "self-educational competence" were analyzed. It is well-founded that selfeducational competence is a professionally significant characteristic of lawyers (attorney, judge, prosecutor, etc.), since their professional activity requires constant independent work with legislative and regulatory documents, which are constantly updated. It is proven that the content of self-educational competence of future lawyers consists of: knowledge about rational planning, organization and implementation of self-educational activities, abilities and skills of self-educational activities, a set of motives for self-educational activities, formation of emotional and volitional qualities, reflective skills. The complex of self-educational skills of future specialists is singled out and considered: educational-organizational, educational-informational, educationalcommunicative, educational-intellectual, which form the basis of self-educational competence. The author's definition of the concept of "self-educational competence of future lawyers" is proposed as a dynamic integrative characteristic of the personality, which is determined by a motivational and valuable attitude to self-education and the desire for self-improvement, which is realized through independent cognitive activity and allows to achieve certain personally significant educational, cultural and professional goals. In the structure of the studied phenomenon, the following: cognitiveoperational, value-motivational, personal-reflective components are distinguished. The knowledge-operational component combines the system of knowledge and skills regarding the implementation of self-education activities, its rational planning, organization and implementation. The value-motivational component reflects the presence of value orientations and a set of motives for self-education. The personal-reflective component characterizes the formation of emotional and volitional qualities of the individual, which are necessary for the implementation of self-educational activities.

Исследованы проблемы формирования самообразовательной компетентности будущих специалистов в образовательном процессе высшего образования. Проанализированы разные подходы к трактовке сущности понятия «самообразовательная компетентность». Обосновано, что самообразовательная компетентность является профессионально значимой характеристикой юристов (адвоката, судьи, прокурора и др.), поскольку их профессиональная деятельность требует постоянной самостоятельной работы с постоянно обновляющимися законодательными и нормативно-правовыми документами. Доказано, что содержание самообразовательной компетентности будущих юристов составляют: знание рационального планирования, организации и осуществления самообразовательной деятельности, умения и навыки самообразовательной деятельности, совокупность мотивов осуществления самообразовательной деятельности, сформированность эмоционально-волевых качеств, рефлексивных умений.
Essence and structure of self-educationsal competence of future lawyers
Keywords: заклади вищої освіти; освітній процес; самоосвітня компетентність; самоосвітня діяльність; майбутні юристи; institutions of higher education; educational process; self-education competence; self-education; future lawyers; заведения высшего образования; образовательный процесс; самообразовательная компетентность; самообразовательная деятельность; будущие юристы